Midwifery Continuity of Care to Support Early Breastfeeding Success: Kesinambungan Asuhan Kebidanan untuk Mendukung Keberhasilan Menyusui Dini - Arcellya, Rosalina Septi; Widowati, Hesty (Universitas Muhammadiyah Sidoarjo, 2025)
Pregnancy, childbirth, postpartum, newborns and family planning are physiological and continuous processes. The aim of providing midwifery care with continuity of care is to use SOAP midwifery management. qualitative descriptive method using a case study approach where Mrs. M was given care starting from TM III pregnancy, childbirth, newborns, postpartum to family planning in a sequence starting from reviewing data, formulating problems, planning care, carrying out care and evaluation, finally documenting using the SOAP method with SOAP development data. Midwifery care in NY. M, 24 year old postpartum mother, first day 6 hours post partum with blood pressure examination results of 110/80, conjunctiva not anemic, perineal suture wound still wet, bleeding less than 100 cc, uterine fundus height 2 fingers below the center and good uterine contractions, breast milk The first day hasn't come out yet. Mothers are advised to breastfeed their babies on demand and as often as possible to stimulate breast milk to come out and do acupressure massage at the PC 6 and GB11 points. For approximately 30 minutes of continuity of care midwifery care for Mrs. M has been done, the problem is slightly resolved. Breast milk slowly comes out, even if only a few drops. It is hoped that the mother will always breastfeed her baby a maximum of every 2 hours for good results. Furthermore, it was concluded that midwifery care provided when breast milk has not yet come in, can be an experience for mothers in order to achieve sustainable breastfeeding success. The hope is that midwives can implement and maintain quality and sustainable service quality in accordance with the SOP. Highlights: Continuity of Care: Midwifery care was provided from late pregnancy to postpartum and contraception using the SOAP method. Early Breastfeeding Support: Immediate postpartum care focused on stimulating breast milk through frequent breastfeeding and acupressure. Quality Midwifery Practice: The experience emphasizes the importance of consistent, SOP-based care to support breastfeeding success. Keywords: Childbirth, Midwifery Care, COC, Acupressure